The effects of global postural re-education on sleep quality and stress in university women lecturers: a randomized controlled trial - Rodríguez-Aragón, Manuel; Barranco-Rodríguez, David; de Mora-Martín, Marta; Sánchez-Jorge, Sandra; Varillas-Delgado, David; Valle-Benítez, Noelia (Frontiers in Psychiatry, 2024)
Objective The present study aimed to evaluate the effect of global postural re-education (GPR) on sleep quality and stress in female health science lecturers. Methods A total of 24 female university lecturers were allocated in this randomized controlled trial into intervention (n = 12) and control (n = 12) groups. The intervention group underwent familiarization and training on the therapy to execute an 8-week treatment with GPR. Data collected on sleep quality were analyzed using 24-h accelerometry (Actigraphy GT3X+) in addition to the Pittsburgh Sleep Quality Index (PSQI) questionnaire score as well as the State-Trait Anxiety Inventory (STAI) anxiety questionnaire. Data on stress were collected by measuring salivary cortisol. Results After comparing the GPR of the groups, there was a main effect of the group (F = 5.278, p = 0.044) for PSQI. The post-hoc analysis revealed that both groups decreased scores between pre- and post-treatment. Additionally, post-treatment, there were differences between groups. For sleep latency, there were main effects of group (F = 6.118, p = 0.031) and score × group (F = 9.343, p = 0.011) interactions. The post-hoc analysis revealed that treatment groups decreased scores between pre- and post-treatment, and there were differences between groups (all p < 0.050). Conclusion The self-administered GPR improves sleep quality in female university lecturers, providing a valuable self-regulation tool for enhanced sleep quality and enhanced academic performance. Further study may help to develop this as a potential tool to help university lecturers' job performance.